Formation of magnesium‐smectite during lacustrine carbonates early diagenesis: Study case of the volcanic crater lake Dziani Dzaha (Mayotte – Indian Ocean). Issue 3 (2nd November 2018) - Milesi, Vincent P.; Jézéquel, Didier; Debure, Mathieu; Cadeau, Pierre; Guyot, François; Sarazin, Gérard; Claret, Francis; Vennin, Emmanuelle; Chaduteau, Carine; Virgone, Aurélien; Gaucher, Eric C.; Ader, Magali
Abstract: The volcanic crater lake of Dziani Dzaha in Mayotte is studied to constrain the geochemical settings and the diagenetic processes at the origin of Mg‐phyllosilicates associated with carbonate rocks. The Dziani Dzaha is characterized by intense primary productivity, volcanic gases bubbling in three locations and a volcanic catchment of phonolitic/alkaline composition. The lake water has an alkalinity of ca 0·2 mol l −1 and pH values of ca 9·3. Cores of the lake sediments reaching up to one metre in length were collected and studied by means of carbon–hydrogen–nitrogen elemental analyzer, X‐ray fluorescence spectrometry and X‐ray powder diffraction. In surface sediments, the content of total organic carbon reaches up to 20 weight %. The mineral content consists of aragonite and hydromagnesite with minor amounts of alkaline feldspar and clinopyroxene from the volcanic catchment. Below 30 cm depth, X‐ray diffraction analyses of the <2 μm clay fraction indicate the presence of a saponite‐like mineral, a Mg‐rich smectite. The saponite‐like mineral accumulates at depth to reach up to ca 30 weight %, concurrent with a decrease of the contents of hydromagnesite and organic matter. Thermodynamic considerations and mineral assemblages suggest that the evolution of the sediment composition resulted from early diagenetic reactions. The formation of the saponite‐like mineral instead of Al‐free Mg‐silicates resulted from high aluminum availability, which is favoured in restricted lacustrine environments hosted in alkaline volcanic terrains commonly emplaced during early stages of continental rifting. Supersaturation of the lake water relative to saponite is especially due to high pH values, themselves derived from high primary productivity. This suggests that a genetic link may exist between saponite and the development of organic‐rich carbonate rocks, which may be fuelled by the input of CO2 ‐rich volcanic gases. This provides novel insights into the composition and formation of saponite‐rich deposits under a specific geodynamic context such as the Cretaceous South Atlantic carbonate reservoirs.